Physicochemical and Sensory Quality of Noodle with Taro and Gembus Flour - Ayustaningwarno, Fitriyono; Velicia, Velicia; Christanto, Monica Lemuela; Indriyanti, Risa; Wijayanti, Hartanti Sandi; Rahadiyanti, Ayu; Afifah, Diana Nur; Rustanti, Ninik; Anjani, Gemala; Ayu, Azzahra Mutiara (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2025)
Consuming low glycemic index (GI) foods is crucial for managing glycemic control in people with diabetes mellitus (DM). Meanwhile, taro (Colocasia esculenta L. Schott) flour, recognized for low GI and resistant starch content, along with gembus flour, rich in fiber and protein, are potential substitutes in the formulation of dried noodle designed for DM diets. This study aimed to investigate five formulations namely F0 to F4 with varying percentages of taro and gembus flour using a completely randomized design. The parameters analyzed include energy content, proximate composition (carbohydrates, protein, fat, moisture, ash), dietary fiber, resistant starch, starch digestibility (using Kjeldahl, Soxhlet, and AACC 66-50 methods), as well as cooking quality. Statistical analysis used Kruskal-Wallis, Mann-Whitney, and one-way analysis of variance (ANOVA) with post-hoc tests to assess differences. Organoleptic quality was evaluated using hedonic and Just About Right (JAR) scales, while GI and glycemic load (GL) were determined by comparing glucose response curves. The results showed that higher gembus flour content reduced energy content, carbohydrates, starch digestibility, and GL, while increasing protein, fat, ash, dietary fiber, resistant starch, and cooking loss. The optimal formulation, F4 (20% taro flour, 20% gembus flour), was favored due to the balanced nutritional profile indicated by lower levels of carbohydrates and fat with higher levels of protein and fiber, as well as consumer preference. In conclusion, substituting taro and gembus flour in dried noodle significantly impacts nutritional composition, cooking quality, organoleptic attributes, and glycemic response, making both suitable alternatives for managing DM dietary needs.